COVID-19 Geospatial Vulnerability Indices and the GeoLAC Repository for Geospatial Data - World Bank (World Bank, Washington, DC, 2020)
The GeoLAC repository contains three maps of the Latin America and the Caribbean (LAC) region that aim to inform policy (governments and the World Bank) around the Coronavirus 2019 (COVID-19) crisis. These maps present three new vulnerability indices that tackle the following topics: (1) expected employment losses in local labor markets; (2) structural socioeconomic vulnerabilities at subnational levels to various forms of shocks (economic, health, etc.); and (3) socioeconomic vulnerabilities at subnational levels specific to the COVID-19 crisis.